Gallbladder lymphoma in a miniature dachshund - NAGATA, Nao (J Vet Med Sci, 2014)
A 7-year-old, miniature dachshund was referred for examination and treatment of persistent anorexia, deep yellow-coloured urine and leucocytosis. The clinical sign of jaundice, results from a serum biochemistry profile and ultrasonographic images suggested a biliary tract obstruction. A cholecystectomy was performed to remove the obstruction. Histopathological assessment of the resected gallbladder and partial common bile duct indicated diffuse large B-cell lymphoma. Twelve days after the initial operation, a second procedure was performed due to bile leakage into the abdominal cavity. Chemotherapy was administered twice after the second operation but discontinued, because the dog showed adverse effects. The dog is still alive 24 months after the surgery. To the authors’ knowledge, this is the first description of canine gallbladder lymphoma.